(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In this article, the effective forms and methods of shaping students’ moral and spiritual education are analyzed based on a scientific-theoretical foundation. Moral and spiritual education is considered an important element in developing individuals’ ethical principles, fostering empathy, and gaining an understanding of life goals. The study discusses the issue of effectively organizing moral and spiritual education processes by harmonizing traditional and modern pedagogical approaches. Specifically, the role of methods such as experiential education, personal role models, moral communication, and social activities in shaping students’ moral values is analyzed in detail. Furthermore, in the context of globalization, the integration of cultural and ritual practices into educational processes is discussed as a way to increase students’ social responsibility and establish a solid moral worldview. The research findings lay the groundwork for developing scientific and methodological recommendations aimed at improving the effectiveness of moral and spiritual education in pedagogical practice